2022
DOI: 10.1042/bsr20212416
|View full text |Cite
|
Sign up to set email alerts
|

Identification of pathological subtypes of early lung adenocarcinoma based on artificial intelligence parameters and CT signs

Abstract: Objective: To explore the value of quantitative parameters of artificial intelligence and computed tomography (CT) signs in identifying pathological subtypes of lung adenocarcinoma appearing as ground-glass nodules (GGNs). Methods: CT images of 224 GGNs from 210 individuals were collected retrospectively and pathologically classified into atypical adenomatous hyperplasia (AAH)/adenocarcinoma in situ (AIS), minimally invasive adenocarcinoma (MIA), and invasive adenocarcinoma (IAC) groups. Artificial intelligenc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(7 citation statements)
references
References 36 publications
1
6
0
Order By: Relevance
“…Recently, a study reported that in terms of artificial intelligence parameters, from AAH/AIS to MIA, and IAC, there was a gradual increase in two-dimensional mean diameter, three-dimensional mean diameter, mean CT value, maximum CT value, and volume of GGNs. Two models that distinguished the pathologic subtypes of LUAD have been developed using AI, and the AUCs of the predictive model for identifying AAH/AIS and MIA and of the model for identifying MIA and IAC were 0.779 and 0.918, respectively ( 22 ). When the diagnostic value of the AI tumor volume was accessed, the AUC of tumor volume based on AI in diagnosing tumor invasiveness was 0.698, which was slightly lower than previously reported findings ( 22 , 24 ).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Recently, a study reported that in terms of artificial intelligence parameters, from AAH/AIS to MIA, and IAC, there was a gradual increase in two-dimensional mean diameter, three-dimensional mean diameter, mean CT value, maximum CT value, and volume of GGNs. Two models that distinguished the pathologic subtypes of LUAD have been developed using AI, and the AUCs of the predictive model for identifying AAH/AIS and MIA and of the model for identifying MIA and IAC were 0.779 and 0.918, respectively ( 22 ). When the diagnostic value of the AI tumor volume was accessed, the AUC of tumor volume based on AI in diagnosing tumor invasiveness was 0.698, which was slightly lower than previously reported findings ( 22 , 24 ).…”
Section: Discussionmentioning
confidence: 99%
“…Two models that distinguished the pathologic subtypes of LUAD have been developed using AI, and the AUCs of the predictive model for identifying AAH/AIS and MIA and of the model for identifying MIA and IAC were 0.779 and 0.918, respectively ( 22 ). When the diagnostic value of the AI tumor volume was accessed, the AUC of tumor volume based on AI in diagnosing tumor invasiveness was 0.698, which was slightly lower than previously reported findings ( 22 , 24 ). Based on the FR + CTC level, tumor invasiveness predictive models have been established.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Such effective classifications are expected to have applications in clinical practice. Fang et al ( 28 ) analyzed CT images of 224 hairy nodules and GGNs from 210 patients. AI identified GGNs using quantitative parameters and CT signs.…”
Section: Applications Of Ai In Lung Cancer Diagnosismentioning
confidence: 99%
“…The CT features, including quantitative and qualitative indicators, were typically used for evaluating the invasiveness of GGNs in previous studies, and have revealed the positive correlations between them [10][11][12]. Among them, the density was more frequently used than others, and both the two-dimensional (2D) and three-dimensional (3D) mean CT values of nodules were effective for further evaluations.…”
Section: Introductionmentioning
confidence: 99%